Houses, convivial meals and tableware at Himera in the 5th century BC - Belvedere, Oscar (Journal of Greek Archaeology, 2023)
After the end of the excavations conducted between the 1960s and 1970s in the upper town of Himera, we took time to reflect on our work, that after other research experiences, the growth of the problems and a new evaluation of the archaeological methodologies, ended after a quarter of a century with the revision of the results of the excavations of Insula II (blocks 1-4), investigated between 1965 and 1967- 69. Revision started in 2001 and was published in 2008 by Nunzio Allegro and his team. More or less in the same years, I too felt the need to review at least in part my excavation activity on the upper town of Imera, carried out in Insula III between 1972-1973, together with Elena Epifanio, and in Insula XII until the end of the 1970s.